Results of bacterial analysis of foodstuffs and swabs from working surfaces in food manufacturing and marketing facilities in Bosnian-Podrinje Canton Goražde - Medina Bičo; Erna Dardagan (Биомедицинска истраживања, 2018)
Introduction: According to the Consumer and Food Safety Act, the term foodstuffs is referred to as any substance used for food or drink, either processed or unprocessed. Food safety is referred to as hygiene food safety as well as the safety of food composition (energy giving, body building and protective food components). The aim of the study is to examine the bacteriological quality of samples of foodstuffs and swabs from working surfaces in food manufacturing and marketing facilities in Bosnian-Podrinje Canton (BPC) from 2011 to 2015, as well as to determine whether the increase in the frequency of supervision leads to the decrease in the number of defective samples. Methods: The study encompassed three municipalities of BPC: Goražde, Prača and Ustikolina. Microbiological quality of samples was tested in the accredited microbiology laboratory of the Public Health Institute of the Sarajevo Canton, and partly in the laboratories of the Public Health Institute of BPC. For a retrospective view of the obtained data, Central laboratory protocols from the last five years were used. Results: The greatest number of samples was collected in catering establishments in Goražde Municipality. The number of analyzed samples increased during five-year period: from 51 food and 69 swab samples in 2011 to 150 food and 270 surface swab samples in 2015. The number of inadequate samples decreased simultaneously from 7.27% to 3.33%. In the majority of samples, aerobic mesophilic bacteria (37) and saprophytic cocci (25) were isolated, while Streptoccocus faecalis and sulphitoreducing Clostridiae were found only in one sample. The number of samples in which bacteria were isolated decreased in five-year period: from 38 samples in 2011 to 15 samples in 2015. Conclusion: It has been shown that the more frequent control of the food manufacturing and marketing facilities leads to better results, that is to the reduction in the number of bacteriological defective samples. Food safety is not alarming in BPC.
Keywords: bacterial; analysis; foodstuffs; swabs; surfaces; food